(untitled) (Jurnal Manajemen dan Investasi (MANIVESTASI), 2025)
ABSTRACT This study aims to determine the effect of motivation, skills and work culture on employee performance partially or simultaneously on employee performance at PT. Kereta Api Indonesia (Persero) Regional Division III Palembang. The population of this research is a population of 40 people and the sample used is all employees in the HR department, totaling 40 people. The data comes from the questionnaire data of employees of PT. Kereta Api Indonesia (Persero) Regional Division III Palembang. Based on data management, it is obtained multiple linear regression equation for motivation variable, skill on employee performance is Y= 1.041 + 0.874 X1 + 0.020X2 + 0.034(X3). Based on the hypothesis test with the t test for the motivation variable, a significant value of 0.000 < alpha 0.05 was obtained, then HO was rejected and Ha was accepted. Thus, partially motivation, which means that there is a significant effect on employee performance for the first hypothesis (H1). Test the hypothesis with the t-test for the skill variable, obtained a significant value of 0.000 < alpha 0.05, then HO is rejected and Ha is accepted. Thus partially skill which means there is a significant effect on employee performance for the second hypothesis (H2). Hypothesis testing with t test for work culture variable obtained a significant value of 0.002 < alpha 0.05 then HO is rejected and Ha is rejected. Thus partially work culture which means there is a significant influence on employee performance for the third hypothesis (H3). The results of the f test hypothesis obtained a significant value of 0.000 < alpha 0.05, meaning that HO was rejected and Ha was accepted. Thus, simultaneously motivation, skills and work culture have an effect on employee performance for the fourth hypotension (H4). Keywords : Motivasi, Skill, Budaya Kerja dan Kinerja Karyawan. ABSTRAK Penelitian ini bertujuan mengetahui pengaruh motivasi, skill dan budaya kerja terhadap kinerja karayawan secara parsial maupun simultan secara bersama-sama terhadap kinerja karyawan pada PT. Kereta Api Indonesia (Persero) Divisi Regional III Palembang. Populasi penelitian ini yang berjumlah populasi 40 orang dan sampel yang digunakan yaitu seluruh karyawan dibagian SDM yang berjumlah 40 orang. Data berasal dari data kuesioner karyawan PT. Kereta Api Indonesia (Persero) Divisi Regional III Palembang. Berdasarkan pengelolaan data diperoleh persamaan regresi linier berganda untuk varibel motivasi, skill terhadap kinerja karyawan adalah Y= 1,041 + 0,874 X1 + 0,020X2 + 0,034(X3). Berdasarkan uji hipotesis dengan uji t untuk variabel motivasi diperoleh nilai signifikan 0,000 < alpha 0,05 maka HO ditolak dan Ha diterima. Dengan demikian secara parsial motivasi yang bearti ada pengaruh signifikan terhadap kinerja pegawai untuk hipotesis pertama (H1).Uji hipotesis dengan uji t untuk variabel skill diperoleh nilai signifikan 0,000 < alpha 0,05 maka HO ditolak dan Ha diterima. Dengan demikian secara parsial skill yang bearti ada pengaruh signifikan terhadap kinerja karyawan untuk hipotesis kedua (H2). Uji hipotesis dengan uji t untuk variabel budaya kerja diperoleh nilai signifikan0,002 < alpha 0,05 maka HO ditolak dan Ha ditolak. Dengan demikian secara parsial budaya kerja yang bearti ada pengaruh signifikan terhadap kinerja karyawan untuk hipotesis ketiga (H3). Hasil hipotesis uji f diperoleh nilai signifikan sebesar 0,000 < alpha 0,05 artinya HOdi tolak dan Ha diterima. Dengan demikian secara simultan motivasi, skill dan budaya kerja berpengaruh secara bersama-sama terhadap kinerja karyawan untuk hipotensis keempat (H4). Keywords : Motivation, Skill, Work Culture and Employee Performance.